The Effectiveness of Field Learning Based on Megapodius reinwardt Ecotourism in Improving the Critical Thinking Skills of Biology Education Students - M. Yamin; A Wahab Jufri; Gunawan Gunawan; Ade Andriyan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The development of critical thinking skills is a strategic agenda in biology education, particularly in preparing prospective teachers capable of integrating scientific analysis with real ecological contexts. However, learning that remains oriented towards classrooms and limited laboratories has not fully strengthened students' evaluative and argumentative abilities. Field learning based on M. reinwardt ecotourism offers a contextual approach that places students in authentic observation and analysis situations. This study aims to test the effectiveness of ecotourism-based field learning in improving the critical thinking skills (CTS) of Biology Education students. The study used a quasi-experimental pretest–posttest control-group design. The experimental group implemented the Ecotourism-Based Field learning Model (EBFL) by studying the ecology and conservation of M. reinwardt in the Gunung Tunak and Kerandangan Nature Tourism Parks, while the control group followed a conventional laboratory practicum. The research instrument was a CTS test validated by experts, and the model's effectiveness was analysed using N-Gain and the Mann–Whitney test. The results showed a significant difference in CTS improvement between the experimental and control groups, as well as a substantive influence of field learning on higher-level cognitive achievement. These findings strengthen the development of an ecotourism-based contextual science learning model as a pedagogical innovation in the education of prospective biology teachers.